2008
DOI: 10.1021/ac7021376
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Impedance Immunosensor Based on Three-Dimensionally Ordered Macroporous Gold Film

Abstract: A novel label-free immunosensor for the detection of C-reactive protein (CRP) was developed based on a three-dimensional ordered macroporous (3DOM) gold film modified electrode by using the electrochemical impedance spectroscopy (EIS) technique. The electrode was electrochemically fabricated with an inverted opal template, making the surface area of the 3DOM gold film up to 14.4 times higher than that of a classical bare flat one, characterized by the cyclic voltammetric (CV) technique. The 3DOM gold film whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
126
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 242 publications
(131 citation statements)
references
References 35 publications
3
126
2
Order By: Relevance
“…To evaluate the electron transfer nature of the modified Au electrode, CV measurements were carried out in 10 mM K 3 [Fe(CN) 6 ]/K 4 [Fe(CN) 6 ] which was used as a redox probe at a scan rate of 50 mV s…”
Section: Characterization Of the Immunosensor Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the electron transfer nature of the modified Au electrode, CV measurements were carried out in 10 mM K 3 [Fe(CN) 6 ]/K 4 [Fe(CN) 6 ] which was used as a redox probe at a scan rate of 50 mV s…”
Section: Characterization Of the Immunosensor Fabricationmentioning
confidence: 99%
“…[1][2][3] Traditional methods used in immunoassays such as radioimmunoassay and enzyme-linked immunosorbent assay are highly sensitive. However, radioimmunoassay exposes laboratory workers to a significant safety hazard, while enzyme-linked immunosorbent assay is tedious and time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in EIS report using alternative electrode materials such as electrically conducting polymers [44,45] and nanoparticles [46,47]. Additionally, electrode geometry has proven important with interdigitated electrode arrays providing improved sensitivity [39,48].…”
Section: Amperometric Sensorsmentioning
confidence: 99%
“…Recently, EIS technique has been developed for studying the fundamental and applied electrochemistry and materials science, including characterization of materials,8 biosensors in sensing of bacterial, DNA or protein,9 corrosion science,10 fuel cell, and batteries 11. Despite these abroad applications, only a few studies have reported on the electrochemical detection of POPs at μ m level by our group,12 which could not satisfy the demand of environmental science.…”
Section: Introductionmentioning
confidence: 99%